Surface plasmon enhanced photoluminescence of monolayer WS₂ on ion beam modified functional substrate - Chu, Lingrui (2021)
Developing efficient methods for boosting light-matter interactions is critical to improve the functionalities of two-dimensional (2D) transition metal dichalcogenides toward next-generation optoelectronic devices. Here, we demonstrate that the light-matter interactions in tungsten disulfide (WS2) monolayer can be significantly enhanced by introducing an air-stable functional substrate (fused silica with embedded plasmonic Ag nanoparticles). Distinctive from conventional strategies, the Ag nanoparticles are embedded under the surface of fused silica via ion implantation, forming a functional substrate for WS2 monolayer with remarkably environmental stability. A tenfold photoluminescence enhancement in WS2 monolayer has been achieved due to the plasmonic effect of Ag nanoparticles. This work offers a strategy to fabricate the plasmon-2D hybrid system at low cost and large scale and paves the way for their applications in optoelectronics and photonics.